2011
DOI: 10.1007/s10620-011-1570-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful Control of Peristomal Infection by Introducer-Type Percutaneous Endoscopic Gastrostomy: A Retrospective Historical Control Study

Abstract: Our results suggest the superiority of the introducer method in terms of infection control. However, the balloon-type catheter is associated with problems such as balloon insufficiency in long-term use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Human studies suggest lower peristomal infection rates when the “introducer” technique is used . This is speculated to be due to the complete avoidance of the oral cavity . Peristomal infection was diagnosed in only 1 dog in our report; however, mild‐to‐moderate peristomal inflammation was observed in all dogs.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Human studies suggest lower peristomal infection rates when the “introducer” technique is used . This is speculated to be due to the complete avoidance of the oral cavity . Peristomal infection was diagnosed in only 1 dog in our report; however, mild‐to‐moderate peristomal inflammation was observed in all dogs.…”
Section: Discussionmentioning
confidence: 54%
“…Traditionally, endoscopic‐assisted gastrostomy tubes are placed by a “pull” technique that involves passage of the tube through the oral cavity during the procedure . Human studies suggest lower peristomal infection rates when the “introducer” technique is used . This is speculated to be due to the complete avoidance of the oral cavity .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional PEG tubes are well secured with a button that is intragastrically located. In contrast, the DP PEG system is fixed with a balloon cuff similar to a Foley catheter and previous authors have reported rates of dislocation of up to 47.8% in long-term follow-up [15,25,26] . We demonstrated that tube dislocation occurs in about 25% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…PEG was carried out using an introducer PEG kit (Cliny PEG Kit; Create Medic, Yokohama, Japan) according to previously described methods. [9] Before insertion of the endoscope, 0.01 to 0.03 mg/kg of midazolam and 50 mg of pethidine were administered intravenously. Upon verification of mild to moderate sedation, 2% lidocaine jelly was applied to the nasal cavities and the DUE was inserted via the transnasal route.…”
Section: Methodsmentioning
confidence: 99%
“…[8] This method has the advantage of reducing postprocedural peristomal infection. [9,10] The use of an ultrathin endoscope improves the patient's comfort, reduces cardiopulmonary risk and has a high success rate. [3,4,10] PEG insertion via the introducer method requires accurate gastric visualization, making it a potential test procedure for DUE evaluation.…”
Section: Introductionmentioning
confidence: 99%